(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In the article, the highest total yield of shallot varieties grown in the soil-climatic conditions of Andijan region is Sprint (44.2 t/ha), Uralsky fioletovy (40.4 t/ha) and Kunak (39.4 t/ha) and the total yield the highest commodity yield in Sprint (42.5 t/ha), Uralsky fioletovy (38.6 t/ha) and Kunak (37.4 t/ha) varieties it is stated that it has been determined.